The relationship between children’s cognitions and later educational progress in rural South Africa: a longitudinal study - Cortina, M; Jack, H; Pearson, R; Kahn, K; Tollman, S; Tintswalo, H; Twine, R; Stein, A; Fazel, M (BMJ Publishing Group, 2019)
Background: Children in low and middle-income countries (LMIC) who remain in school have better health and employment outcomes. South Africa, like many LMIC, has a secondary school completion rate under 50%, leaving room for improvement if we can identify factors that affect educational attainment. This is the first longitudinal study to examine the effects of childhood mental health and cognitions on educational outcomes in LMIC. Methods: Using the Strengths and Difficulties Questionnaire (SDQ) and Cognitive Triad Inventory for Children (CTI-C), we assessed the psychological functioning and cognition of children aged 10-12 in rural South Africa. We linked that data with measures of educational progress collected five years later and examined associations between educational progress and 1) behavioural and emotional problems and 2) cognitive interpretations, adjusting for possible confounders. Results: Educational data was available for 443 individuals. 92% (n= 408) of individuals had advanced three or fewer grades in seven years. Having more positive cognitions (CTIC-C) was positively associated with progressing at least three grade levels (adjusted OR: 1.43; 95% CI: 1.14-1.79). There was no evidence for an association between emotional and behavioural problems (SDQ) and educational progress (OR: 0.90; 95% CI: 0.72-1.11). Conclusion: If children in LMIC can develop more positive perspectives, they may be able to stay in school longer. Cognitions can be modified, and future studies should test interventions that work to improve cognition in childhood, guided , for example, by principles of cognitive behavioral therapy.